(untitled) (Hoboken, N.J., 2006)
In The Credit Market Handbook, financial expert and Editor H. Gifford Fong has assembled a group of prominent professionals and academics familiar with the credit arena. In each chapter, a different expert analyzes a different issue related to today's dynamic credit market, including portfolio credit risk, valuation models, and the importance of modeling credit default.
Keywords: Credit,Risk management,Default (Finance); Mathematical models,Mathematical models,Mathematical models